PREVALENCE OF MENTAL DISORDERS AMONG OLDER PEOPLE - Gázquez Linares, José Jesús; Pérez Fuentes, María del Carmen; Lucas Acién, Francisca; Yuste Rossell, Nazario (Anales de Psicología / Annals of Psychology, 2008)
In our country, there are not many researches which analyze in a general way, the mental disorders prevailing within the older people. So, the purpose of this research was focused in the analysis of more common disorders in older people who require psychological and/or psychiatric help. For this purpose, it was analyzed the medical history of 2,054 people of more than 60 years old who went to the District Mental Health Department within the last 10 years and were diagnosed according to the criteria of diagnosis given by the ICD-10. The results obtained showed that the disorders for what those people went to the Mental Health Department, more frequently old people, were neurotic due to stressful situations and somatomorphic disorders, emotional disorders and organic mental disorders including symptomatic. Men are only above of women in mental and behavioral disorders due to the consumption of psychotrop substances and behavioral disorders due to physiological malfunctions and physical factors. Likewise, divorced or separated men have a higher consumption of psychotrop substances together with several personality disorders. Finally, it is important to highlight that there is a direct connection between the age increase and the prevalence of organic mental disorders including symptomatic disorders.